Exciton-induced lattice defect formation - Savchenko, E.V.; Ogurtsov, A.N.; Zimmerer, G. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2003)
The lattice defect formation in solid Ne induced by electronic excitation was studied using the selective vacuum ultraviolet spectroscopy method. The samples were excited with synchrotron radiation in the range of excitonic absorption n = 2Г(3/2). The dose dependence of the intensity distribution in the band of atomic type self-trapped exciton luminescence was analyzed. A direct evidence of the formation and accumulation of point lattice defects in solid Ne via the excitonic mechanism was obtained for the first time. The model of the permanent lattice defect formation is discussed.